Structural insights into mouse anti-apoptotic Bcl-xl reveal affinity for Beclin 1 and gossypol - Priyadarshi, Amit; Roy, Ankoor; Kim, Key Sun; Kim, Eunice EunKyeong; Hwang, Kwang Yeon (Academic Press, 2010)
This study reports the crystal structures of Bcl-xl wild type and three Bcl-xl mutants (Y101A, F105A, and R139A) with amino acid substitutions in the hydrophobic groove of the Bcl-xl BH3 domain An additional 12 ordered residues were observed in a highly flexible loop between the alpha 1 and alpha 2 helices, and were recognized as an important deamidation site for the regulation of apoptosis The autophagy-effector protein, Beclin 1, contains a novel BH3 domain (residues 101-125), which binds to the surface cleft of Bcl-xl, as confirmed by nuclear magnetic resonance (NMR) spectroscopy and analytical gel-filtration results Gossypol, a potent inhibitor of Bcl-xl, had a K-d value of 0 9 mu M In addition, the structural and biochemical analysis of five Bcl-xl substitution mutants will provide structural insights into the design and development of anti-cancer drugs (C) 2010 Elsevier Inc All rights reserved